Molecular identification of the ompL1 gene within Leptospira interrogans standard serovars - Mehrangiz Dezhbord; Majid Esmaelizad; Pejvak Khaki; Fariba Fotohi; Athena Zarehparvar Moghaddam (Journal of Infection in Developing Countries)
Introduction: Leptospirosis, caused by infection with pathogenic Leptospira species, is one of the most prevalent zoonotic diseases in the world. Current leptospiral vaccines are mainly multivalent dead whole-cell mixtures made of several local dominant serovars. Therefore, design and construction of an efficient recombinant vaccine for leptospirosis control is very important. OmpL1 is an immunogenic porin protein that could be of special significance in vaccination and serodiagnosis for leptospirosis. Methodology: Three strains belonging to pathogenic L. interrogans were analyzed. The specific primers for proliferation of the ompL1 gene were designed. The amplified gene was cloned. In order to investigate the ompL1 nucleotide sequence and homological analysis of this gene, ompL1 genes cloned from standard vaccinal Leptospira serovars prevalent in Iran were sequenced and cloned. Results: PCR amplification of the ompL1 gene using the designed primers resulted in a 963 bp ompL1 gene product. The PCR based on the ompL1 gene detected all pathogenic reference serovars of Leptospira spp. tested. Based on alignment and phylogenetic analysis, although the ompL1 nucleotide sequence was slightly different within three vaccinal serovars (100%-85% identity), amino acid alignment of the OmpL1 proteins revealed that there would be inconsiderable difference among them. Conclusion: The ompL1 gene of the three isolates was well conserved, differing only by a total of 6 bp and the proteins by 2 amino acids. The cloned gene could be further used for expression and recombinant OmpL1 as an efficient and conserved antigen, and may be a useful vaccine candidate against leptospirosis in our region.